(+/−)-Dievodialetins A−G: Seven pairs of enantiomeric coumarin dimers with anti-acetylcholinesterase activity from the roots of Evodia lepta Merr. (February 2021) - Huang, Guo-Yong; Cui, Hui; Lu, Xin-Yi; Zhang, Lu-Di; Ding, Xiao-Ying; Wu, Jin-Jun; Duan, Li-Xin; Zhang, Shi-Jie; Liu, Zhongqiu; Zhang, Rong-Rong
Abstract: Seven pairs of undescribed enantiomeric bis-coumarins, (±)-dievodialetins A−G, were separated from the roots of Evodia lepta Merr. Two coumarin nuclei were linked via a 1, 4-dimethyl4-vinylcyclohexene moiety in (±)-dievodialetins C−G. The structures of the undescribed compounds, including their absolute configurations were elucidated by spectroscopic analyses, X-ray diffraction, and computational calculations. In the biosynthetic pathways, these bis-coumarins were presumably derived from the precursors demethylsuberosin and 3-(3-methylbut-2-enyl)umbelliferone via a [4 + 2] Diels-Alder reaction. Besides, all compounds exhibited neuroprotective effects by inhibiting acetylcholinesterase (AChE) activity with IC50 values ranging from 7.3 to 12.1 nM and they also suppressed oxidative stress (MDA and SOD) and neuroinflammation (IL-1β and IL-6). Graphical abstract: (±)-dievodialetins A−G, seven pairs of undescribed enantiomeric bis-coumarins were separated from the roots of Evodia lepta Merr., which exhibited neuroprotective effects by inhibiting acetylcholinesterase (AChE) activity. Image 1 Highlights: Seven pairs of undescribed enantiomeric bis-coumarins were identified from the roots of Evodia lepta Merr. All compounds exhibited neuroprotective effects by inhibiting acetylcholinesterase (AChE) activity in SH-SY5Y cells. The antioxidative stress and neuroinflammation effects of all compounds are also evaluated.